2018
DOI: 10.1002/ecy.2381
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying fear effects on prey demography in nature

Abstract: In recent years, it has been argued that the effect of predator fear exacts a greater demographic toll on prey populations than the direct killing of prey. However, efforts to quantify the effects of fear have primarily relied on experiments that replace predators with predator cues. Interpretation of these experiments must consider two important caveats: (1) the magnitude of experimenter-induced predator cues may not be realistically comparable to those of the prey's natural sensory environment, and (2) given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 73 publications
0
53
0
Order By: Relevance
“…An important consideration when assessing the effects of fear on prey populations using predator cues is that the magnitude of those cues may be artificially enhanced by the experimental setup, making them difficult to compare with cues in the prey's natural environment (Peers et al. ). Turbulent, high‐flow conditions may rapidly dilute predator cues in aquatic environments, with prey showing low response levels to predator presence in field conditions compared to laboratory trials (Freeman , McKay and Heck , Harding and Scheibling ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important consideration when assessing the effects of fear on prey populations using predator cues is that the magnitude of those cues may be artificially enhanced by the experimental setup, making them difficult to compare with cues in the prey's natural environment (Peers et al. ). Turbulent, high‐flow conditions may rapidly dilute predator cues in aquatic environments, with prey showing low response levels to predator presence in field conditions compared to laboratory trials (Freeman , McKay and Heck , Harding and Scheibling ).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical cues have been shown to trigger different behavioral responses in several species of sea urchin (Vadas and Elner 2003, Freeman 2006, Matassa 2010, Morishita and Barreto 2011, and seem to play a key role in subtidal ecosystems where invertebrates are important grazers (Haggerty et al 2018). An important consideration when assessing the effects of fear on prey populations using predator cues is that the magnitude of those cues may be artificially enhanced by the experimental setup, making them difficult to compare with cues in the prey's natural environment (Peers et al 2018). Turbulent, high-flow conditions may rapidly dilute predator cues in aquatic environments, with prey showing low response levels to predator presence in field conditions compared to laboratory trials (Freeman 2006, McKay and Heck 2008, Harding and Scheibling 2015.…”
Section: Fig 3 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…, Peers et al. ), is amenable to experimental testing and should be tested in cyclic rodent populations (see also Appendix ). Results of a modelling study by Radchuk et al. () suggested that both intrinsic and extrinsic factors may be necessary to explain rodent population cycles adequately, yet few attempts have been made to test the multifactorial hypothesis due to logistical difficulties. It is widely accepted that population cycles are accompanied by several life‐history and behavioural traits that vary across cyclic phases.…”
Section: What Have We Learned and Where Do We Go From Here?mentioning
confidence: 99%
“…Untangling risk effects in wild populations requires controlling for bottom–up effects (Vucetich and Peterson , DeWitt et al ), yet individual condition, predation risk, and recruitment are rarely measured over the same spatial or temporal scales for wild mammals (Creel et al , Middleton et al ). Thus, while the nature and consequences of NCEs have been well described in elegant experimental systems (reviewed by Preisser et al 2005, Preisser and Bolnick , Schmitz et al ), few studies have explored how animals allocate resources to growth and reproduction under the risk of predation in natural ecosystems (Creel and Christianson , Peers et al ).…”
Section: Introductionmentioning
confidence: 99%